Research on Large-Scale Social Network Graph Data Mining in Telecommunication - Lijiao Liu; Juncai Tao; Xiaojun Xiao; Yu Lu (Dianxin kexue)
With the development of the telecommunications technology, telephone call network almost covered the whole society; the huge social network presents tremendous opportunities for telecommunication companies. Especially in the increasing fierce market competition, more and more telecommunication companies are concerned on maintaining customer relationship, mining customer potential value and marketing suitable target customers. The distribute and stand-alone graph computing frameworks and tools were researched for mining large-scale social network graph data like telecommunication network, and at the end the feasibility and usability of Graphchi in large-scale graph datasets were verified and a graph mining application was made with telecommunication data using stand-alone graph data processing tool—Graphchi.